Search for charge-parity violation in semileptonically tagged D0 → K+π− decays - Aaij, Roel; Bachmann, Sebastian; Carus, Leon; Caspary, Rowina; Celani, Sara; Cocha Toapaxi, Carlos; De Cian, Michel; Dittmann, Lucas; Esen, Sevda; Glaser, Fabian; Günther, Paul André; Han, Xiaoxue; et al. (Journal of high energy physics, 2025)
An analysis of the flavour oscillations of the charmed neutral meson is presented. The ratio of D0 → K+π− and D0 → K−π+ decay rates is measured as a function of the decay time of the D0 meson and compared with the charge-conjugated system to search for charge-parity violation. The meson flavour at production is double-tagged by the charges of the muon and pion in the preceding B overline → D∗(2010)+μ−X and D∗(2010)+ → D0π+ decays, respectively. These decays are selected from proton-proton collision data collected by the LHCb experiment at a centre-of-mass energy of 13 TeV and corresponding to an integrated luminosity of 5.4 fb−1. The flavour oscillation parameters, relating to the differences in mass and width of the mass eigenstates, are found to be y′ = (5.8 ± 1.6) × 10−3 and (x′)2 = (0.0 ± 1.2) × 10−4. No evidence for charge-parity violation is seen either in the flavour oscillations or in the decay, where the direct charge-parity asymmetry is measured to be AD = (2.3 ± 1.7) %.